Patient's Days - Mendoza Fernández, Alfonso (2010)
The Patients Day celebration, a proposal made by our Dean, Professor Ciro Maguiña-Vargas, is an opportunity for expressing solidarity with sick persons, and it is also a time for integration between healthcare personnel and patients. The main objective of this day is to promote in every health facility activities reinforcing the importance of maintaining good health, meditating on the meaning of being a patient, and to continue with this great crusade for humanization of healthcare services and the improvement of healthcare services, since healthcare is a fundamental human right.